Phylogenetic analysis of Middle-Late Miocene apes. Issue 165 (April 2022) - Pugh, Kelsey D.
Abstract: Despite intensive study, many aspects of the evolutionary history of great apes and humans (Hominidae) are not well understood. In particular, the phylogenetic relationships of many fossil taxa remain poorly resolved. This study aims to provide an updated hypothesis of phylogenetic relationships for Middle-Late Miocene fossil apes, focusing on those taxa typically considered to be great apes. The character matrix compiled here samples 274 characters from the skull, dentition, and postcranium. Multiple iterations were performed to examine the effects of ingroup taxon selection, outgroup constraints, treatment of continuous data, character partitions (craniodental, postcranial), and missing data. Parsimony and Bayesian methods were used to infer phylogenetic relationships. Most European hominoids ( Hispanopithecus, Rudapithecus, Dryopithecus, Pierolapithecus ) are recovered as stem hominids, not more closely related to orangutans or to African apes and humans (Homininae), whereas Ouranopithecus, Graecopithecus, and Nakalipithecus are inferred to be members of the hominine clade. Asian fossil hominoids, with the exception of Lufengpithecus hudienensis, are recovered as part of the orangutan clade (Ponginae). Results suggest that Kenyapithecus and Griphopithecus are possible stem hominids, whereas Equatorius and Nacholapithecus are consistently recovered as stem hominoids. Oreopithecus and Samburupithecus are not recovered as hominids. Results of Bayesian analyses differ from those of parsimony analyses. Craniodental and postcranial character partitions are incongruent in the placement of hylobatids, which is interpreted as evidence that hylobatids and hominids independently evolved adaptations to suspensory positional behaviors. An understanding of phylogenetic relationships is necessary to address many of the questions asked in paleoanthropology. Thus, the updated hypothesis of phylogenetic relationships presented here can be used to gain a better understanding of important morphological transitions that took place during hominid evolution, ancestral morphotypes at key nodes, and the biogeography of the clade.